A key distribution protocol based on quantum entanglement swapping for unmanned surface vehicle. Issue 1 (July 2021) - Qin, Lingyu; Li, Ying; Wang, Shibo
Abstract: Aiming at the problem of Unmanned Surface Vehicle's (USV) secure communication, this paper proposes a key distribution protocol based on quantum entanglement swapping for USV. Compared with the current techniques, this paper uses the principle of quantum unclonability and quantum entanglement in quantum mechanics to realize the secure communication of USV. Meanwhile, in view of the low visibility at sea and the influence of weather such as wind and waves, this study adopts a key distribution architecture of quantum relay to realize the establishment of quantum channel between any two ships and obtain the absolutely secure key eventually. Therefore, the proposed method can provide long-distance, secure and reliable communication for USVs in the civil and military fields.